Geochemical evaluation of fluoride contamination of groundwater in the Thoothukudi District of Tamilnadu, India - Singaraja, C.; Chidambaram, S.; Anandhan, P.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R.; Sarathidasan, J. (SpringerOpen, 2014)
Fluoride is a chemical element that has been shown to cause significant effects on human health through drinking water. Different forms of fluoride exposure are of importance and have shown to affect the body’s fluoride content and thus increasing the risks of fluoride-prone diseases. Fluoride has beneficial effects on teeth; however, low concentrations of fluoride intensify the risk of tooth decay. Fluoride can also be quite detrimental at higher concentrations at skeletal fluorosis. The Thoothukudi District is a hard rock and alluvial plain marked as one of the Fluoride-increase area in Tamilnadu due to occurrence of various rock types including fluoride-bearing minerals. The F− content of groundwater can thus originate from the dissolution of Fluoride-bearing minerals in the bed rock. Hundred representative groundwater samples from Thoothukudi District were collected during two different seasons. Samples were analysed for F−, other major cations and anions. The study area is chiefly composed of hornblende biotite gneiss, charnockite, alluvio marine, fluvial marine and granite with small patches of quartzite and sandstone. Higher concentration of fluoride is observed during pre-monsoon (3.3 mg l–1) compared to the post-monsoon (2.4 mg l–1) due to the dilution effect. Spatial distribution and factor score show that higher concentrations of F− are noted in the north and central part of the study area owing to lithology. Bicarbonate is well correlated with F− which explains that both ions were derived from the weathering. While F− has a very weak correlation with pH which may be due to the increase of alkalinity resulting from the increase of carbonate and bicarbonate ions.